Development and evaluation of electronically controlled precision seed-metering device for direct-seeded paddy planter - P RAJAIAH; INDRA MANI; ADARSH KUMAR; SATISH D LANDE; ASHOK KUMAR SINGH; CINI VERGESE (The Indian Journal of Agricultural Sciences, 2016)
An electronic experimental set-up was developed to evaluate three seed-metering mechanisms, viz. slanting, semi- circular and rectangular shape for three paddy varieties and to investigate the influence of the selected levels of variables, viz. forward speed, cell shape and inclination of seed-metering plate on performance parameters of seed- metering. Mean seed spacing, miss index and seed damage were found to increase with increase in forward speed and angle of inclination while multiple index decreased with increase in forward speed and angle of inclination for all metering plates tested. Precision decreased with increase in forward speed and with increase in angle of inclination, it increased initially up to optimum value and then decreased. The mean seed spacing of 14.8 cm close to theoretical seed spacing of 15 cm, highest quality feed index of 88.1%, lowest miss index of 6.1% and minimum seed damage of 0.38% were observed in slanting type metering plate at an angle of 35º with the horizontal and at a forward speed (belt speed) of 2 km/h. Hence, for design of precision paddy planter, the optimum parameters, like slanting type metering plate with angle of inclination 35º and forward speed of 2 km/h can be used to achieve best results.